ETIOLOGY OF FAILURE OF QORI AND QORI'AH OF KERINCI DISTRICT IN MTQ EVENT - Admizal, Iril; Zuhdi, Ahmad; Jalwis (Fakultas Ushuluddin Adab dan Dakwah Insitut Agama Islam Negeri Kerinci, 2025)
The condition of the results of the MTQ (Musabaqah Tilawatil Qur'an) in Kerinci Regency, the achievements obtained are very worrying. In the Decree (SK) issued by the Council of Judges in 2023, Kerinci Regency is in the last position, namely in 10th position out of 10 districts and cities that take part in the MTQ (Musabaqah Tilawatil Qur'an) event. In the recitation branch competition, there are 8 group branches that are contested. Of the eight competitions in the recitation branch category, Kerinci Regency only managed to win two titles, and even then they were runners-up. The aim of this research is to improve the current condition of MTQ results, and the focus of this research is the causes and strategies to change the existing situation. The method used is field research by visiting the object to be studied directly to obtain data that is directly related to the discussion that will be discussed. There are several supporting factors that can improve MTQ performance, namely: first, training. It is needed to hone the skills of qori and qori'ah. Second, government support. Government support is needed both in terms of material and non-material. Third, completeness of facilities. Another supporting factor is that the facilities provided must be adequate so that qori and qori'ah can be comfortable in studying and honing their abilities in the art of reading the Koran. The conclusion is that the factors that cause the performance of Qori and Qori'ah in Kerinci Regency are in a very worrying condition, in fact for the last three years Kerinci Regency has been in the last rank, the cause is due to the lack of adequate facilities and infrastructure provided by the Kerinci Regency and the lack of attention from the government both on services to qori and qori'ah and lack of appreciation so that there is no strong motivation from qori and qori'ah.